The effect of ultraviolet light on biorepulsive hydrogel poly(ethylene glycol) films - Zhao, Zhiyong; Yan, Rui; Zharnikov, Michael (ACS applied polymer materials, 2021)
We studied the eﬀect of ultraviolet (UV) light (254 nm) on porous poly(ethylene glycol) (PEG) ﬁlms, formed by cross-linking of the epoxide- and amino-terminated four-arm STAR-PEG compounds. The major eﬀect of irradiation is progressive decomposition of the PEG material followed by immediate desorption of the released fragments. The removal of the PEG material can be coarsely described by zero-order kinetics with a rate constant of 0.32 ± 0.05 nm/(J/cm2). Surprisingly, this process does not aﬀect the chemical composition of the residual ﬁlm, which preserves all the useful properties of the original PEG material, including its hydrogel character and biorepulsion behavior, which is in striking contrast to the eﬀect of electron irradiation on the PEG ﬁlms and the eﬀect of UV irradiation on oligo(ethylene glycol) (OEG)-substituted self-assembled monolayers, for which the removal of the PEG/OEG material is accompanied by substantial chemical modiﬁcation of the residual part, losing its original properties. The behavior of the PEG ﬁlms under UV irradiation is not only an interesting and unexpected phenomenon but can also be applied to three-dimensional patterning of PEG materials, with the preservation of biorepulsive properties over the entire patterns, which can be potentially useful for applications.
Gesehen am 22.08.2021